Establishment of an Inferred Reference Range for Blood Ammonia in Dogs and Cats Using a Point-of-Care Assay - Giulia Specchia; Emily Hannah Doran Seidel; Charlotte Dye (Veterinary Sciences, 2025)
Point-of-care (POC) tests for blood ammonia (BA) measurement have not been well evaluated in veterinary species. This cross-sectional study sought to establish an inferred reference interval for BA using a POC analyser in dogs and cats. Blood ammonia was measured in 175 dogs and 63 cats for which relevant clinical history and laboratory data was available. Reference values were inferred based on comparisons between patients with and without disease pathologies reported to cause BA elevation. Descriptive statistics, Pearson Chi2, and Mann–Whitney U testing were used to assess for associations between clinical parameters and BA concentration. Seventy-one percent (124/175) of dogs and forty-six percent (29/63) of cats had undetectable BA. Following the exclusion of dogs with potential causes of hyperammonaemia, all remaining dogs had BA < 30 µg/dL. With one exception, all dogs with BA > 30 µg/dL had liver disease. All dogs with a clinical suspicion of hepatic encephalopathy (HE) had BA > 40 µg/dL. Following the exclusion of cats with potential causes of hyperammonaemia, all remaining cats had BA < 25 µg/dL. Only 50% of cats with BA > 25 µg/dL had liver disease. All cats with a clinical suspicion of HE had BA > 30 µg/dL. Based on this study population, BA < 30 µg/dL and <25 µg/dL should be considered normal in dogs and cats, respectively. Additionally, dogs with BA > 30 µg/dL are likely to have liver disease, while cats with BA > 25 µg/dL appear to exhibit a wider variety of disease pathologies.